Development of a cutting edge temperature measurement of end mill tool by using infrared radiation technique - Abdullah, Yassin; Abang Mohammad Nizam, Abang Kamaruddin; Syed Tarmizi, Syed Shazali; M. Shahidul, Islam; Mohd Azrin, Mohd Said; Mohd A., Kiprawi (Universiti Malaysia Pahang, Malaysia, 2019)
This paper describes the development of cutting temperature measurement of end mill tool by using infrared radiation technique approach. Compared to conventional thermocouple technique, infrared radiation technique is an advance method of measuring temperature which featured high accuracy, high response rate, wide range of temperature scale detection and almost compatible with all materials used in the manufacturing industry. We measures the emission of infrared radiation from the source, which is cutting edge of tool by using photocells that contains InAs and InSb photovoltaic detectors. Photocells converts the infrared radiation to a voltage signal and then recorded by oscilloscope followed with a calibration with its corresponding temperature. This paper discussed about the calibration method, cutting experiment setup, the limit of infrared radiation level detected by photocells, signal correction of output signal, and relations of peak signal formation with rotation of end mill tool. The developed pyrometer is also capable to profile the cutting tool’s rotation based on the movements of infrared radiation’s emission at cutting tool’s edge. The conclusion was that the measurement of cutting temperature of high speed machining by using infrared radiation technique is possible. The developed pyrometer are capable to detect temperature changes at a span of 0.01 ms.